Optimasi AHP dalam mendukung UMKM di Bangka Belitung dalam memanfaatkan E-Commerce - Magdalena, Hilyah; Irawadi, Syafrul (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
E-commerce is a breakthrough in doing business in a digital platform that offers many advantages over conventional business transactions. Indonesia as a country with the sixth largest internet users trying to use the internet as a new way of doing business. The Indonesian government also seriously supports e-commerce with the issuance of Presidential Regulation No. 74 of 2017 in August 2017 on electronic map of electronic commerce (Road Map E-Commerce) of the Year 2017-2019. With great support from the Government, e-commerce can improve business transactions in Indonesia including for small and medium businesses in Bangka Belitung. Currently UMKM business development is quite good but not many who take advantage of e-commerce as a way to improve and expand the business. This study aims to analyze the factors that encourage or hamper business actors in Bangka Belitung SME utilizing e-commerce. This research uses Analytical Hierarchy Process (AHP) methodology to construct hierarchically those factors. This research produces several factors that become the main concern of business in utilizing e-commerce, that is technology constraint with weight 33,2%, with sub most influential criteria is information technology mastery factor with weight equal to 38,6%. While the type of business is the most widely is a typical food production business that reaches weight of 38.8%.